How Economic Tropes Affect Attitudes Toward Social Welfare Policies. Issue 3 (27th May 2019) - Rose, Alexander S.; Rose, Randall L.; Lamberton, Cait
ABSTRACT: We offer a framework for understanding public responses to social programs designed to alleviate disadvantages experienced by some sectors of the U.S. population. The framework is built on 2 key tropes of generalized exchange theory: mutuality and possessive individualism. Using the Affordable Care Act (ACA) as a public sector context, we show how marketing messages can be manipulated to affect consumer likelihood to participate in and support the public policy. Consistent with cognitive attitude models, we find that beliefs regarding individual and mutual benefits are significant, positive predictors of ACA attitudes. In contrast, when messages are framed with ideological economic tropes—possessive individualism or mutuality—ACA attitudes diverge. Priming possessive individualism negatively affects program attitudes relative to a mutuality prime or a no-prime control condition. We conclude with policy advice for those tasked with effective implementation of public sector programs.